Acute infection with Brachyspira hyodysenteriae affects mucin expression, glycosylation, and fecal MUC5AC - Lin, Susanne Je-Han; Helm, Emma T.; Gabler, Nicholas K.; Burrough, Eric R. (Frontiers in Cellular and Infection Microbiology, 2023)
Infection with strongly β-hemolytic strains of Brachyspira hyodysenteriae leads to swine dysentery (SD), a production-limiting disease that causes mucohemorrhagic diarrhea and typhlocolitis in pigs. This pathogen has strong chemotactic activity toward mucin, and infected pigs often have a disorganized mucus layer. Herein we demonstrate that colonic mucin glycosylation during SD has an overall increase in fucose, a spatially different distribution of N-acetylglucosamine with more expression within the crypt lumens of the upper colonic mucosa, and decreased expression or a decreased trend of sialic acids in α-2,6 or α-2,3 linkages, and N-glycolylneuraminic acid. Fucose consumption by commensal bacteria is critical to gut microbiota establishment, but also provides nutrients for pathogens. Fucose is a chemoattractant for B. hyodysenteriae and may play a role in the pathogenesis of SD. Diet composition often has a significant impact on SD susceptibility and resolution, and a highly fermentable fiber diet can mitigate and delay the onset of SD. Herein we found that the degree of fucosylation was decreased in the colonic mucosa of pigs infected with SD and fed with such diet, which may be one factor impacting disease development. MUC5AC is secretory mucin that is not constitutively expressed in the colon but shows marked de novo expression in pigs infected with SD. We used a commercial enzyme-linked immunosorbent assay to quantify fecal MUC5AC in infected pigs and assess its potential as a diagnostic monitoring tool. There was a significant increase in MUC5AC in fecal and colonic samples of pigs infected with SD at the endpoint compared to the controls, but the predictive value for disease progression was limited, possibly due to the presence of other non-colonic sources of MUC5AC in the feces. We also used RNA in situ hybridization to detect IL-17A in the colonic mucosa and demonstrated a moderate correlation between IL-17A, neutrophils, and MUC5AC, which confirms its immunoregulatory and mucin stimulatory role as previously proposed. Our study characterizes local alteration of mucin glycosylation in the colonic mucosa of pigs with SD after B. hyodysenteriae infection and may provide insight into host-pathogen interaction.